(untitled) (Journal of Nepal Geological Society, 2019)
The study was carried out in the Lesser Himalaya between Ridi-Shantipur area of the Gulmi District, west-central Nepal. Two geological units: the Nourpul Formation and the Dhading Dolomite were mapped in the area. These units belong to the Nawakot Group as explained by several researchers in central Nepal. The Nourpul Formation can further be divided into three members based on distinct mappable lithology, which are named as the Lower Member, the Middle Member and the Upper Member, respectively. The area is highly folded with several local and regional anticlines and synclines; Ridi Khola Anticline, Ridi-Karikot Syncline, Ruru Anticline, Baletaksar-Gwadi Syncline, Huga-Bamgha Anticline, Rimuwa-Rudrabeni Syncline, Juhan-Eksing Anticline, Juniya-Limgha Syncline, Bharse-Thaple Anticline, and Chiureko Syncline, respectively from the south to the north. All the folds are trending along to the ESE-WNW direction. The origin of these folds can be linked with the thrust propagation in the Himalaya that can be explained with the deformation event D4. The Harewa Khola Thrust is the only one regional scale thrust mapped in the area. The thrust carries the older Nourpul Formation over the Dhading Dolomite with the indications of thrust related features like slickensides and fault-breccias. The thrust seems to propagate to the north. There is a continuous shear zone mapped in the outcrops from the Tal Khola-Aslewa-Eksingh-Gudrung-Juhang- Rupakot region as an indicator of the presence of the Badi Gad Fault in the region.